Judicial oversight of administrative control authorities in normal circumstances (Journal of Imam Al-Kadhim College, 2023)
Abctract:The function of administrative control is one of the old jobs as old as the state itself, as it is “one of the oldest functions carried out by the state since ancient history until know time, and also” it is one of the necessary and necessary functions to protect society as a whole, and also one of the functions that are used to protect and protect public order within the state. , whether in normal circumstances or in exceptional circumstances, since without the function of administrative control, chaos prevails, turmoil prevails, and the balance is disturbed in society. The function of administrative control has expanded in the modern time, both for developing countries that “administrative control is largely a tool of governance, and as for the developed countries in which administrative control has become a means of management to ensure that individuals respect the state’s systems and laws, the function of administrative control is one of the first The duties of the state and the most important of them, as “the function of administrative control is a social necessity that we see in all modern societies, and this is due to the fact that preventing harm is more successful than treating it after it has occurred.